Advisory Panel's Tax Reform Proposals. (U.S. Congressional Research., 2006)
Describes and compares two tax reform proposals formulated by the President's Advisory Panel on Tax Reform, one to create a simplified income tax and the other to create a growth and investment tax. Analyzes both proposals based on revenue neutrality, simplicity and administrative feasibility, fairness and equity, and a variety of economic effects; and discusses transition issues. Includes tables.